2015
DOI: 10.1111/jgs.13827
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Nativity, and Disability in Older Mexican Americans

Abstract: Background/Objectives Although older Mexican Americans are a rapidly growing segment of the U.S population, with high rates of disability, there is presently little research examining nativity and sex differences in activities of daily living (ADL) and mobility limitations in older Mexican Americans compared to general studies of the older population. This study examined the effect of nativity and sex on ADL and mobility limitations in older Mexican Americans. Design, Setting, Participants, Measurements 2,06… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…Our results for ADL disability are consistent with previous findings that show a significant interaction effect between gender and nativity among Mexican Americans aged 75 years and older, with foreign-born males less likely to report any ADL disability relative to their U.S.-born counterparts (Hayward et al, 2014; Nam et al, 2015). However, this finding contradicts results from Melvin et al (2014), which document a foreign-born male disadvantage in ADL disability in older age-groups (75–84 and 85+).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results for ADL disability are consistent with previous findings that show a significant interaction effect between gender and nativity among Mexican Americans aged 75 years and older, with foreign-born males less likely to report any ADL disability relative to their U.S.-born counterparts (Hayward et al, 2014; Nam et al, 2015). However, this finding contradicts results from Melvin et al (2014), which document a foreign-born male disadvantage in ADL disability in older age-groups (75–84 and 85+).…”
Section: Discussionsupporting
confidence: 92%
“…The models were fit to males and females separately to account for well-known gender differences in the age patterns of disability. Prior research has found a complex interplay between gender and nativity among the U.S. Mexican-origin population (Angel et al, 2001, 2014; Garcia et al, 2015; Nam, Al Shih, & Markides, 2015). Mexican-origin women live longer than men and have a greater opportunity to experience health problems (Angel et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Thus, these findings on significant predictors of mortality can assist medical researchers, clinicians and policymakers in long-term planning to help older Mexican Americans remain healthy and free of disability, age successfully, and enjoy better quality of life. 21 The present study was subject to several limitations. First, it did not examine survival effects.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, in contemplating preventive medicine, determining long‐term mortality risk factors could help adults live longer and healthier lives even from late middle age. As compared with the general population, Mexican Americans are living longer (a life expectancy of 81.6 years) than white (79.1 years) and black (75.5 years) Americans, but older Mexican Americans are experiencing high rates of severe obesity, diabetes and disability . Thus, these findings on significant predictors of mortality can assist medical researchers, clinicians and policymakers in long‐term planning to help older Mexican Americans remain healthy and free of disability, age successfully, and enjoy better quality of life …”
Section: Discussionmentioning
confidence: 99%